Binding energies of hypernuclei and hypernuclear interactions - Bodmer, A. R.; Murall, S.; Usmanis, Q. N. (HNPS Advances in Nuclear Physics, 2020)
In part 1 the effect of nuclear core dynamics cm the binding energies of Λ hy pernuclei is discussed in the framework of variational correlated wave functions. In particular, we discuss a new rearrangement energy contribution and its effect on the core polarization. In part 2 we consider the interpretation of the Λ single-particle energy in terms of basic Λ-nuclear interactions using a local density approximation based on a fermi hypernetted chain calculation of the Λ binding to nuclear matter. To account for the data strongly repulsive 3-body AN Ν forces are required. Also in this framework we discuss core polarization for medium and heavier hypernuclei.